Nursing Care of Premature Rupture of Membranes in Pregnancy: Roy Adaptation Model - Restuning Widiasih; Mira Trisyani; Ida Maryati; Yanti Hermayanti (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Premature rupture of membranes (PROM) is a condition associated with spontaneous rupture of the amniotic membranes before any signs of the active labour. It increases the risk of complications on maternal and foetal health. In preventing various complications that would arise due to PROM, nurses should apply an appropriate nursing theories or models in developing the nursing care plan. Nursing theories and conceptual models are the nursing knowledge that organize nursing activities, and guide nurses in research, practice, education, and management. However, in Indonesia, nursing models have rarely been used by nurse practitioners and researchers including in the perinatal periods. The aim of this article was to determine the application of Roy’s adaptation theory in the premature rupture of membranes cases. This study was a case study design. There were 5 pregnant women participate in this study. The results showed that the assessment based on the two adaptation model approaches applied in this study, six nursing diagnosis were identified, and all nursing care plan had implemented. The concept of adaptation was appropriate in helping patient with premature rupture of membranes. However, the social aspect related to the client's cultural practices were not describe clearly. Combining two or more theories in a nursing care plan would benefit to mothers and their babies’ health and welfare. Keywords: Nursing theories, Premature rupture of membranes, pregnancy, complications